Answer:
- To solve these first swap x and y, solve for y and name it inverse function
3. y = -8x + 2
- x = -8y + 2
- 8y = -x + 2
- y = -x/8 + 2/8
- y = -(18)x + 1/4
f⁻¹(x) = -(18)x + 1/4
-----------------------------------------
4. y = (2/3)x - 5
- x = (2/3)y - 5
- (2/3)y = x + 5
- y = (3/2)x + (3/2)5
- y = 1.5x + 7.5
f⁻¹(x) = 1.5x + 7.5
-----------------------------------------
5. f(x) = 2x² - 6
- x = 2y² - 6
- 2y² = x + 6
- y² = 1/2x + 3
- y =
f⁻¹(x) =
-----------------------------------------
6. y = (x - 3)²
- x = (y - 3)²
= y - 3- y = 3 +
f⁻¹(x) = 3 +